Global profiling and inhibition of protein lipidation in vector andhost stages of the sleeping sickness parasite Trypanosoma brucei - Wright,MH; Paape,D; Price,HP; Smith,DF; Tate,EW (ACS Infectious Diseases, 2016)
The enzyme N-myristoyltransferase (NMT) catalyses the essential fatty acylation ofsubstrate proteins with myristic acid in eukaryotes and is a validated drug target in theparasite Trypanosoma brucei, the causative agent of African trypanosomiasis (sleepingsickness). N-Myristoylation typically mediates membrane localisation of proteins and isessential to the function of many. However, only a handful of proteins are experimentallyvalidated as N-myristoylated in T. brucei. Here, we perform metabolic labelling with analkyne-tagged myristic acid analogue, enabling the capture of lipidated proteins in insect and host life stages of T. brucei. We further compare this with a longer chain palmitate analogueto explore the chain length-specific incorporation of fatty acids into proteins. Finally, wecombine the alkynyl-myristate analogue with NMT inhibitors and quantitative chemicalproteomics to globally define N-myristoylated proteins in the clinically relevant bloodstreamform parasites. This analysis reveals five ARF family small GTPases, calpain-like proteins,phosphatases and many uncharacterized proteins as substrates of NMT in the parasite,providing a global view of the scope of this important protein modification and furtherevidence for the crucial and pleiotropic role of NMT in the cell.